PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, AUDITOR SWITCHING, DAN KOMITE AUDIT TERHADAP AUDIT DELAY: (Studi Empiris Pada Perusahaan Sektor Property Dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2023) - Fresheila Thisa Aurelia; Triana Anggraini (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
The study aims to determine the influence of Profitability, Company Size, Auditor Switching, and Audit Committee on Audit Delay in Property and Real Estate Sector Companies Listed on the Indonesia Stock Exchange for the 2018-2023 period. The population of this study is Property and Real Estate Sector Companies listed on the Indonesia Stock Exchange for the 2018-2023 period with sampling using a technique, namely the purposive sampling method with certain criteria and a sample of 48 companies was obtained. This study uses multiple linear regression analysis methods with the help of the Package of Social Science (SPSS) Version 25 program. The results show that the profitability variable has a negative effect on Audit Delay, Company Size has no effect on Audit Delay, Auditor Switching has no effect on Audit Delay, and Audit Committee has no effect on Audit Delay.